Etnomatematika; Eksplorasi Transformasi Geometri Pada Ragam Hias Cagar Budaya Khas Yogyakarta - Abdullah, Ahmad Anis (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2020)
Abstract The results of the achievements of Indonesian students in the 2018 Program for International Student Assessment (PISA) show that Indonesian students' mathematical abilities are still below average. One of the reasons for the low PISA Indonesia 2018 results is that students are not used to non-routine questions, students are more interested in solving questions according to the material but do not understand contextual questions. In addition, many students think that mathematics is one of the solutions to this problem is learning that is difficult and boring. Based on these problems, an interesting and contextual mathematics learning approach is needed according to the mandate of the 2013 curriculum. One of them is by learning mathematics based on local culture or better known as ethnomatematics. This research is a descriptive study with an ethnographic approach to geometry material which is one of the contents of PISA. The purpose of this study is to explore the concepts of geometric transformation in the decoration of buildings of a typical cultural heritage of Yogyakarta. The results showed that the variety of decorations in Yogyakarta-specific cultural heritage buildings contained geometric transformation concepts including translation (shift), reflection (reflection), rotation (rotation), and dilation (multiplication). Keywords: ethnomatematics, decoration, geometric transformation. Abstrak Hasil prestasi siswa Indonesia pada Programme for International Student Assesment (PISA) 2018 menunjukkan kemampuan matematika siswa indonesia masih di bawah rata-rata. Salah satu alasan rendahnya hasil PISA Indonesia 2018 adalah siswa tidak terbiasa dengan soal non-rutin, siswa lebih tertarik menyelesaikan soal sesuai materi tetapi kurang memahami soal yang bersifat kontekstual. Selain itu banyak siswa yang beranggapan bahwa matematika adalah Salah satu solusi dari permasalahan ini adalah pembelajaran yang sulit dan membosankan. Berdasarkan permasalahan tersebut, dibutuhkan pendekatan pembelajaran matematika yang menarik dan kontekstual sesuai amanat kurikulum 2013. Salah satunya dengan pembelajaran matematika berbasis budaya lokal atau lebih dikenal dengat etnomatematika. Penelitian ini merupakan penelitian deskriptif dengan pendekatan etnografi pada materi geometri yang menjadi salah satu konten dari PISA.Tujuan dari penelitian ini untuk melakukan eksplorasi konsep-konsep transformasi geometri pada ragam hias bangunan cagar budaya khas Yogyakarta. Hasil Penelitian menunjukkan bahwa ragam hiasan pada bangunan cagar budaya khas Yogyakarta mengandung konsep-konsep transformasi geometri yang meliputi translasi (pergeseran), refleksi (pencerminan), rotasi (perputaran), dan dilatasi (perkalian). Kata Kunci: etnomatematika, ragam hias, transformasi geometri